EXAMINING THE IMPACT OF EXCHANGE RATE REGIMES ON INFLATION IN NIGERIA - Gbenga Adeyemi (International Studies Journal)
This study empirically examining the impact of exchange rate regimes on inflation in Nigeria. Using quarterly secondary data, it was structured from 1981 to 1986 for fixed exchange rate and also 1987 to 2023 for managed flexible exchange rate. The variables used were Consumer price index (cpi) that captured inflation as dependent variable while Nominal exchange rate (nexrt), fixed and managed flexible exchange rate, and real gross domestic product (rgdp) as an independent variable. The variables were tested for the unit root test, both the ADF and PP unit root tests established that all the variables were stationary at both level (I(0)) for CPI and  first differencing (I(1)) for nexrt and rgdp. The ARDL Bounds indicated test that there exists a long run relationship among the variables, they were co-integrated. The result of the open economy fixed exchange rate model shows that the co-efficient of output gap is -0.1146 and it was found to be statistically significant, it  means that there is a trade-off between inflation and Unemployment during the fixed exchange rate regime while the result also showed that the managed flexible exchange rate regime is characterized by an output gap of 1.2920, which was found to be statistical insignificant, it means that there is absence of trade-off between inflation and unemployment during manage flexible exchange rate regime because a stronger positive relationship between inflation and unemployment may indicate stagflation pressure, where both inflation and unemployment rise simultaneously. In conclusion, managed flexible exchange rate regime is more impacted positively than fixed exchange rate regime. The study recommends that the Monetary authority should put more effort to control Nominal Exchange rate so that it would not cause inflation in Nigeria by supplying adequate US$ into Nigeria foreign exchange market when necessary.